Mesh skin graft and digital pad transfer to reconstruct the weight-bearing surface in a dog - Rahal, Sheila Canevese [UNESP]; Mortari, Ana C. [UNESP]; Morishin Filho, Milton M. [UNESP] (My University, 2007)
A 2-month-old dog was presented with injuries involving both hind paws. Only the 5th digit and its digital pad were present on the right paw. Following a full-thickness skin graft, the 5th digital pad was transferred distal to the metatarsal bones. The transferred pad permitted weight-bearing on the limb.
Keywords: animal; animal disease; case report; dog; foot injury; hindlimb; injury; male; methodology; physiology; skin transplantation; treatment outcome; weight bearing; wound healing; Animals; Dogs; Foot Injuries; Hindlimb; Male; Skin Transplantation; Treatment Outcome; Weight-Bearing; Wound Healing; Canis familiaris